PERTUMBUHAN TUNAS PADA BULB ANGGREK HITAM (COELEGYNE PANDURATA LINDLEY 1853) - Sasongko, Dwi Agus (Universitas Nusa Bangsa, 2019)
Black orchid (Coelegyne pandurata Lindley 1853) is one of the natural resources that are vulnerable to forest destruction. Efforts to save black orchids need to be done in various ways of cultivation. The vegetative method is one option that can be done. This method produces puppies with the exact same characteristics as the parent. Black orchid is a type of sympodial orchid that makes it possible to do the bulb separation as the parent material. Bulb separation is a simple way that can be done by all groups. This study aims to determine the time of growth of shoots resulting from the separation of bulbs from the parent family. Bulb selected in conditions without active roots, without leaves, and without any treatment. These minimum conditions will be a critical factor in the ability of black orchids to maintain their survival. The results showed that with minimalist terms, black orchid was able to sprout within 26-29 days after bulb separation.